2022
DOI: 10.1186/s13256-022-03459-8
|View full text |Cite
|
Sign up to set email alerts
|

Deep venous thrombosis and acute pericarditis associated with severe acute respiratory syndrome coronavirus 2 infection in a Congolese infant with sickle cell disease: a case report

Abstract: Background Since the beginning of the pandemic, no severe pediatric coronavirus disease 2019 cases have been described in Congo. Case We studied a 3-month-old male child of Congolese origin who was admitted to the pediatric department with 7-day history of fever, unilateral lower leg swelling, and dyspnea. There was no known history of contact with a coronavirus disease 2019 patient, and all the family members were asymptomatic. Nasopharyngeal swab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In fact, the hypercoagulability state typical of sickle cell disease and the capacity of COVID-19 to promote thromboembolic events are listed as reasons that could explain the possibly higher risk of adverse outcomes of the infection ( 52 , 72 , 99 ). Some studies suggest an elevated incidence of pulmonary embolism in people with sickle cell disease and COVID-19 ( 16 , 43 , 53 , 72 , 79 , 103 ). However, case series, such as those conducted by Mitchell et al ( 60 ) and Noisette et al ( 62 ), present divergent data in this regard.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the hypercoagulability state typical of sickle cell disease and the capacity of COVID-19 to promote thromboembolic events are listed as reasons that could explain the possibly higher risk of adverse outcomes of the infection ( 52 , 72 , 99 ). Some studies suggest an elevated incidence of pulmonary embolism in people with sickle cell disease and COVID-19 ( 16 , 43 , 53 , 72 , 79 , 103 ). However, case series, such as those conducted by Mitchell et al ( 60 ) and Noisette et al ( 62 ), present divergent data in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, there is no consensus when it comes to prophylactic anticoagulation. Many authors consider it plausible to intensify these regimens among sickle cell patients, given the potentially increased risk for coagulation disorders in this group ( 94 , 103 ). Others, such as Singh et al ( 108 ), facing the evidence that the risks are similar to those observed in the general population, suggest that anticoagulation should be carried out rationally, following the guidelines adopted in each institution.…”
Section: Discussionmentioning
confidence: 99%